Commission on Center State Report Part II - Planning Commission (Planning Commission, 1987)
The Commission will examine and review the working of the existing arrangements between the Union and States in regard to powers, functions and responsibilities in all spheres and recommend such changes or other measures as may be appropriate. In examining and reviewing the working of the existing arrangements between the Union and States and making recommendations as to the changes and measures needed, the Commission will keep in view the social and economic developments that have taken place over the years and have due regard to the scheme and framework of the Constitution which the founding fathers have so sedulously designed to protect the independence and ensure the unity and integrity of the country which is of paramount importance for promoting the welfare of the people”.
Report
Government of India